THE ROLE OF SOCIAL SERVICES IN IMPLEMENTING THE FULFILLMENT OF THE RIGHT TO EDUCATION FOR CHILDREN NEGLECTED DUE TO DIVORCE IN BOYOLALI REGENCY - Aditya Denny Permana; M. Junaidi (CV. Lafadz Jaya, 2026)
This study aims to examine the role of the Social Service Agency of Boyolali Regency in implementing basic social rehabilitation outside institutional care in fulfilling the right to education for neglected children caused by parental divorce and to identify the challenges faced in its implementation. The research method used is empirical juridical with a socio-legal approach through primary data obtained from interviews and secondary data from literature and relevant regulations. The findings show that the Social Service Agency of Boyolali Regency has implemented various services such as family-based care, social assistance, social assistance programs, temporary shelter services, and referrals to childcare institutions to support the fulfillment of children’s basic needs. The discussion also reveals that the fulfillment of children’s right to education is carried out through affirmative education pathways and inter-agency coordination to ensure children can continue accessing formal education. The main challenges identified include difficulties in determining the status of neglected children, dependence on the condition of family-based care, and complex inter-agency coordination.